Determinants Of Supply Chain Manager’s Skills: The Mediating Effect Of Personal Cognitive Ability - Wulansari, Puspita (2020)
The purpose of this study is to explain the influence of determinant factors on supply chain manager’s skills. |Determinant factors consist of environment issue, training and development, supply chain integration, supply chain responsiveness, hiring and recruiting, and information technology. Whereas, supply chain manager’s skills consist of understand law, ethics and regulation skills, communication skills, and technology skill. This study also investigated the cognitive ability of supply chain manager as a mediating factor. This research is based on a quantitative research conducted in global manufacturing industries in Indonesia.